Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 46. Beitrag. Odonata. - Bilek, Alois (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The present paper reports on the Odonata found by the expedition to Albania by Deutsches Entomologisches Institut; in addition, all finds are compiled that were made in Albania so far. The passages in small print deal with all other species known from the adjacent countries, part of which can be assumed to exist also in Albania. The expedition by DEI collected 65 individuals of 17 species, 3 species being new in Albania. Thus a total of 39 Odonata species is now known from the People’s Republic of Albania. The adjacent parts of Yugoslavia (Montenegro, Serbia, Macedonia) and Greece have 21 more species.